Improved quality of colon cancer surveillance after implementation of a personalized surveillance schedule. Issue 3 (14th May 2020) - Rueff, Jessica; Weixler, Benjamin; Viehl, Carsten T.; Ochsner, Alex; Warschkow, Rene; Gueller, Ulrich; Mingrone, Walter; Zuber, Markus
Abstract: Background: Early detection of recurrence through surveillance after curative surgery for primary colon cancer is recommended. We previously reported inadequate quality of surveillance among patients operated for colon cancer. These poor results led to the introduction of a personalized surveillance schedule. This study reassesses the quality of surveillance after the introduction of the personalized schedule. Patients and Methods: A total of 93 patients undergoing curative surgery for colon cancer between January 2009 and December 2014 (prospective data registration) were included in this retrospective single‐center cohort study. Written informed consent was given by all patients. Compliance with surveillance was compared with national guidelines, as well as with the previous results and analyzed depending on where surveillance was conducted (general practitioner or outpatient clinic). Results: Adherence to surveillance was higher when performed by oncologists compared to general practitioners with an odds ratio (OR), 6.03 (95%CI: 3.41‐10.67, P  = .001). Compared with the previous study, adherence to surveillance was significantly higher in the later cohort with an OR = 4.55 (95%CI: 2.50‐8.33, P  < 0.001). Conclusion: This study demonstrates that the implementation of a personalized surveillance schedule improves adherence to recommendations and that awareness can be increased with this simple measure.